Ice Pile-Up on Shores in Northwestern Lake Ontario during Winter 1990 - Gilbert, Robert (Géographie physique et Quaternaire, 1991)
ABSTRACTTwo wind-driven ice pile-up events occurred at small islands in northwestern Lake Ontario in winter 1990, the first, an unusual, mid-winter event on 24 January and the second on 17 March at breakup. Both occurred during periods of warm weather which weakened and thinned the ice sheet so that moderate winds were able to drive part of the ice cover offshore. Soon after, onshore winds drove the ice back where it piled in shallow water along the islands. In both cases the volume of ice pile-up exceeded 104 m3, but was very limited in extent and had little geomorphic effect on the coasts.